Problem Based Learning Innovation Using Analog Clock Learning Media To Improve Student Learning Outcomes on Time Concept Materials in Elementary School - Umami, Nafisatun; Wardono, Wardono (International Journal of Education, Information Technology, and Others, 2025)
The purpose of this study is to find out how effective the problem-based learning model (PBL) that uses analog clock media in improving student learning outcomes in time concept materials in elementary and elementary schools. This study uses an experimental method with a pre-test-post-test control group design. The experimental group that used PBL with analog clock media and the experimental group that used PBL without analog clock media consisted of two classes. The results showed that the experimental group obtained an average posttest score of 85.7, then the control group obtained a score of 74.3. As per the t-test, there was a significant difference between the two groups (p <0.05). In addition, the student attendance rate in the experimental class reached 85%, while in the control class only obtained 65%. The feedback of the students was very positive, 90% of them enjoyed and benefited from the use of PBL and analog clock media, in addition to their understanding of the concept of time also improved. This study shows that the combination of PBL and concrete visual media significantly improves students' learning achievement, motivation, and interest. Therefore, it is highly recommended to teach mathematical concepts, especially those that must be visualized, in elementary school.